1987
DOI: 10.1111/j.1600-0404.1987.tb03537.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigations into multiple sclerosis in Southern Hesse. V. Course and prognosis

Abstract: Course and possible prognostic predictors were studied retrospectively in 363 MS patients collected during an epidemiological study. The proportion of patients showing a primarily progressive course was 18%; 19% of patients of more than 10 years duration showed a benign course, and 8% of those of less than 16 years duration, a malignant course. Although benign cases were twice as frequent in females as in males, the difference between both sexes was not significant. A primarily or secondarily progressive cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
2
11
0
2
Order By: Relevance
“…In line with our results, previously published data indicate that an RR course of MS is strongly correlated with a better prognosis, whereas the prognosis seems to be poorer for both an SP and PP course [4,6,24,25]. In some previous studies, the prognosis was found to be favourable when only one functional system was affected [26,27]. Our results are in accordance with these findings.…”
Section: Discussionsupporting
confidence: 83%
“…In line with our results, previously published data indicate that an RR course of MS is strongly correlated with a better prognosis, whereas the prognosis seems to be poorer for both an SP and PP course [4,6,24,25]. In some previous studies, the prognosis was found to be favourable when only one functional system was affected [26,27]. Our results are in accordance with these findings.…”
Section: Discussionsupporting
confidence: 83%
“…CIS patients presenting with motor symptoms have a risk of secondary progression 2.0 times higher and a risk of being wheelchair-bound after 25 years 2.8 times higher than patients with purely sensory symptoms (Eriksson et al, 2003). Similarly, patients with motor, sphincter, cerebellar, spinal cord, or multiregional involvement at onset have also been reported to have worse outcomes than patients without these features (Lauer and Firnhaber, 1987;Phadke, 1990;Bergamaschi et al, 2005;Ebers, 2005).…”
Section: Disabilitymentioning
confidence: 94%
“…8,15,34 ONS data have been used to estimate the increase in mean age at death from MS since the 1950s. The data are presented in Figure 6.…”
Section: Estimates Of Changes In Prevalence With Timementioning
confidence: 99%